Determination of spray volume index for culture of coffee - Sousa, Jose Marcio Sousa; Alves Ruas, Renato Adriane Alves Ruas Adriane; Silva, Carlos Diego Silva Diego; Faria, Vinícius Ribeiro Faria Ribeiro; Carvalho Filho, Alberto Carvalho Filho; Vieira, Lucas Caixeta Vieira Caixeta (Coffee Science - ISSN 1984-3909, 2017)
The adjustment of the spray volume according to the volume of vegetation has exhibited a way to make the most efficient pesticide applications. However, for the adoption of this method for the coffee, the determination of the volume index is still needed. Thus, the aim was to determine the volumetric rate of spraying for coffee (Coffea arabica ). The treatments were arranged in blocks following factorial (5 x 5), five spray volumes (200, 300, 500, 600 and 800 L ha-1) and five vegetative volume (TRV) with four replicates. We conducted the evaluation of leaf density prior to the application of treatments in three development stages (filling, maturation and post-harvest fruit). We analyzed the spray deposition (SD), density of the droplets (DD), the volumetric median diameter (VMD) of the droplets and relative amplitude (SPAN) of droplet spectrum. The applied spray volumes were converted to volumetric index (VI). There was no interaction between TRV and water volume (p> 0.05) for the variables SD and DD answers. In the evaluation performed during the maturation stage, leaf density was 29% higher at the time of post-harvest and the maximum SD obtained was 0.74 cm 2 uL. The VMD medium obtained was 217 m and the span 1,1. The adjustment of the curve DD according VI allowed to estimate a reduction of up to 47% of the spray volume applied. It was concluded that the VI set according to the changes in leaf density reduces the spray volume applied to coffee plantations.